2003
DOI: 10.1074/jbc.m212262200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Properties of Mammalian Neutral Sphingomyelinase2 and Its Role in Sphingolipid Metabolism

Abstract: Neutral sphingomyelinase (N-SMase) is one of the key enzymes involved in the generation of ceramide; however, the gene(s) encoding for the mammalian N-SMase is still not well defined. Previous studies on the cloned nSMase1 had shown that the protein acts primarily as lyso-platelet-activating factor-phospholipase C. Recently the cloning of another putative N-SMase, nSMase2, was reported. In this study, biochemical characterization of the mouse nSMase2 was carried out using the overexpressed protein in yeast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
181
1
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(203 citation statements)
references
References 53 publications
(68 reference statements)
19
181
1
1
Order By: Relevance
“…1 A very recent report demonstrated that endogenous nSMase2 levels are induced upon confluence and are involved in induction of cell cycle arrest in MCF7 cells. 40,41 Furthermore, nSMase overexpression and treatment with cell-permeable ceramide analogues can induce growth arrest in a number of cells types including SK-Hep1, 6 U937 7 and HT-29. 8 Over 1000 research papers have described the induction of programmed cell death (apoptosis) by interventions that elevate the cell content of ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…1 A very recent report demonstrated that endogenous nSMase2 levels are induced upon confluence and are involved in induction of cell cycle arrest in MCF7 cells. 40,41 Furthermore, nSMase overexpression and treatment with cell-permeable ceramide analogues can induce growth arrest in a number of cells types including SK-Hep1, 6 U937 7 and HT-29. 8 Over 1000 research papers have described the induction of programmed cell death (apoptosis) by interventions that elevate the cell content of ceramide.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic defects in several of these hydrolytic enzymes cause various disorders with lysosomal accumulation of the substrate lipids, a group of disorders termed the sphingolipidoses [41,[90][91][92][93]. Particularly, some of the known sphingolipidoses might closely associate with aberrant metabolisms of ceramide because of defective activities of ceramide generating/degrading enzymes: Farber's disease, Gaucher disease, and Niemann-Pick type A and B diseases are caused by a deficiency of acid ceramidase [94,95], glucocerebrosidase (acid-β-glucosidase) [96][97][98], acid SMase [99,100], respectively. The salvage pathway is one of the routes for controlling cellular levels of ceramide.…”
Section: Sphingolipidosesmentioning
confidence: 99%
“…This effect of Smpd3 knockdown against expression of Col2a1 was mimicked by the addition of 1 M GW4869, a specific inhibitor compound for nSMase (Fig. 3B) (49), suggesting that the data from the siSmpd3 experiment resulted from down-regulation of nSMase2. GW4869 also enhanced the production of the cartilage-specific extracellular component, glycosaminoglycan, by BMP-2 stimulation for 17 days, as assessed by Alcian blue staining, both in ATDC5 cells and in primary chondrocytes (Fig.…”
Section: Bmp-2-induced Increase Of Smpd3 Expression Is Runx2-dependenmentioning
confidence: 99%